Global Unions, Global Business: Global Union Federations and International Business - McIlroy, John (Labour / Le Travail, 2010)
The article reviews the book, "Global Unions, Global Business: Global Union Federations and International Business," by Richard Croucher and Elizabeth Cotton.
Keywords: BOOKS – Reviews; COTTON; Elizabeth; CROUCHER; Richard; GLOBAL Unions; Global Business: Global Union Federations & International Business (Book); INTERNATIONAL labor activities; Nonfiction

Canada - Palmer, Bryan D. (Histories of Labour: National and International Perspectives, 2010)
A survey of the global trajectory of labour history. Specially commissioned essays by labour historians of international repute consider: early labour history traditions, new conceptions of class, gender, ethnicity, culture, community and power. Whether the 1960s can be regarded as turning point in labour history the general historiographical climate in the mid-twentieth century the institutional context (e.g. the evolution of labour history societies, historical associations and journals) links between labour history and the labour movement Many authors are connected with the British Society for the Study of Labour History; all are experts in the labour history of particular countries. They analyse key debates, question dominant paradigms, acknowledge minority critiques and consider future directions. –Publisher's description.
OCLC: ocn520744842
Keywords: Historiography; History; Labor; Labor movement; Working class